Estacionalidad poblacional de los estados inmaduros de Aedes albifasciatus (Djptera: Culicidae) en la provincia de Buenos Aires, Argentina - García, Juan José; Micieli, María Victoria (Revista de Biología Tropical, 2000)
Aedes albifasciatus. a floodwater mosquito, is widely distributed in freshwater habitats in Argentina. At high population densities it is an important pest in urban areas. A two year study was conducted in a natural population of A. albifasciatus around La Plata area, Buenos Aires province, Argentina. The breeding site was weekly sampled from May, 1996 to April, 1998. Immature stages of A. albifasciatus were collected with a standard 300 mI dipper. Each sample unit consisled of 100 dipper. Highest den sities of mosquito larvae occurred when the breeding site was flooded among 90 and 100 % ofits capacity after remaining dry for several days or weeks. The larvae required between six and eight days lo become adult in summer (temperature mean 24.6 oC in January and 21.3 oC in February). In autumn-winter, 43 days (temperature mean 10.6 oC) and in spring 22 days (temperature mean 15.5 oC).